The ERA: A Brave New World of Accountability for Australian University Accounting Schools - De Lange, Paul; O'Connell, B.; Mathews, M.; Sangster, A. (Wiley-Blackwell Publishing Asia, 2010)
This study examines the potential impact of Excellence in Research for Australia (ERA) on Australian university accounting schools through a series of in-depth interviews with Heads of Schools. Using an institutional theory framework we find that the pending introduction of the ERA has brought about changes in school structures, processes and systems. A creeping isomorphism is apparent as evidenced by a sector-wide movement towards targeting publications in highly ranked North American journals. While participants were generally positive about the overall aims of the ERA many felt that it would marginalise non-mainstream research. Furthermore, they were of the opinion that the ERA would lead to a reduction in the standing of accounting schools within Australian universities relative to other disciplines.